Penerapan Metode Pembelajaran Problem Based Learning Untuk Meningkatkan Pemahaman Siswa Kelas X B SMKN 1 Wewewa Barat Dalam Pengukuran Tahanan Listrik Pada Mata Pelajaran Dasar Listrik Dan Elektronika - Seingo Bili, Dominggus (CV. Multi Kreasi Media, 2024)
This study aims to improve the understanding of Class XB students at SMKN 1 Wewewa Barat in the Basic Electricity and Electronics subject, particularly on the topic of measuring electrical resistance, through the implementation of the Problem-Based Learning (PBL) method. This research uses a classroom action research approach with two improvement cycles. In the pre-cycle, the average student score was 68.27 with a mastery percentage of 39.29%, indicating a need for improvement in material comprehension. Cycle I applied PBL, resulting in an increase in the average score to 75.50 and a mastery percentage of 64.29%. Adjustments in Cycle II showed significant improvement, with the average student score reaching 81.77 and the mastery percentage rising to 92.86%. These data indicate that the PBL method is effective in enhancing students' understanding of electrical resistance measurement. This study recommends further implementation of the PBL method and continuous adjustments for more optimal results.